Relating Visual Disability and the Web - Baguma, Rehema; Bommel, Patrick van; Wanyama, Tom; Patrick, Ogao (ITA, 2007)
Despite the fact that the proportion of people with disabilities in society has been increasing, many critical online public activities are not readily available to them. Much as a large body of literature has examined the overall impact of visual disability on functional status and quality of life including Web usage, few published studies have explicitly investigated the relationship between visual disability and Web-based tasks. Moreover, the available Web Accessibility guidelines to-date lack coherence and simplicity for easy comprehension and application in Web application design for different disability groups. For example the primary reference guidelines – that is the Web Content accessibility guidelines (WCAG) is organized arbitrarily with no distinct sections according to types of disabilities covered. This makes such guidelines hard to understand and apply by Web content developers. This paper examines how properties of Web applications affect users with various visual disabilities. The goal of this study was to understand the problems faced by Web users with visual disabilities and how the problems can be addressed in Web development tasks. Understanding the relationship between visual disability and Web applications is an important foundation for further research considerations on how to make the Web more accessible to people with visual disabilities. Such considerations may include but not limited to: development of concise visual accessibility indicators and associated design techniques. The paper is organized into six sections namely: introduction; methodology; related work, properties of Visual disability and Web applications, the relationship between visual disability and properties of Web applications; Conclusion and future Work.
Keywords: Visual Disability; Web Application; Web Accessibility; Design Guidelines